The Concept of Tawakal in the Perspective of Sufism: An Analysis of Ibn Atha’illah’s Thought in the Book of Al-Hikam - Ana Rohmatul Wafiroh; Aoulia; Siti Komariah; Siti Komariah; Sifa Latifah; Ajeng Wundari; Abdul Yamin; Cecep Ubaidillah; Moch. Mahdiyan Nasikhin (Edumaspul: Jurnal Pendidikan, 2026)
This study examines the concept of tawakkal from a Sufi perspective through the analysis of the thought of Ibn ’Atha’illah al-Sakandari in Al-Hikam. The background of this research lies in the frequent distortions of tawakkal in modern society, which is often interpreted as passive fatalism that ignores human effort or as an over-reliance on rational efforts that ignores the spiritual dimension. This research aims to provide a comprehensive conceptual understanding of tawakkal and analyze its relevance in addressing contemporary psychological and existential challenges. This research uses a qualitative approach with library research methods, using conceptual and interpretive frameworks. Primary data sources include Al-Hikam, the Qur’an, and Hadith, while secondary sources consist of classical Sufi works and contemporary studies on religiosity and mental health. The findings reveal that tawakkal, according to Ibn ’Atha’illah, is not a neglect of effort but a state of the heart that is detached from dependence on worldly causes while continuing to make optimal efforts (endeavor). Tawakkal serves as an integrative principle that harmonizes effort and surrender, offering a critique of fatalistic and materialistic tendencies. In addition, tawakkal has significant psychological implications, including reducing anxiety, strengthening emotional resilience, and fostering inner peace in the midst of uncertainty. In conclusion, tawakkal in Al-Hikam represents a holistic spiritual-ethical concept that is theologically based and relevant as a psycho-spiritual coping mechanism in modern life. Abstrak Penelitian ini mengkaji konsep tawakkal dari perspektif Sufi melalui analisis pemikiran Ibnu ’Atha’illah al-Sakandari dalam Al-Hikam. Latar belakang penelitian ini terletak pada seringnya distorsi tawakkal dalam masyarakat modern, di mana sering diartikan sebagai fatalisme pasif yang mengabaikan upaya manusia atau sebagai ketergantungan berlebihan pada upaya rasional yang mengabaikan dimensi spiritual. Penelitian ini bertujuan untuk memberikan pemahaman konseptual yang komprehensif tentang tawakkal dan menganalisis relevansinya dalam mengatasi tantangan psikologis dan eksistensial kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian perpustakaan, menggunakan kerangka konseptual dan interpretatif. Sumber data primer termasuk Al-Hikam, Al-Qur’an, dan Hadis, sedangkan sumber sekunder terdiri dari karya-karya Sufi klasik dan studi kontemporer tentang religiusitas dan kesehatan mental. Temuan tersebut mengungkapkan bahwa tawakkal, menurut Ibnu ’Atha’illah, bukanlah pengabaian usaha tetapi keadaan hati yang terlepas dari ketergantungan pada sebab-sebab duniawi sambil terus melakukan upaya yang optimal (ikhtiar). Tawakkal berfungsi sebagai prinsip integratif yang menyelaraskan upaya dan penyerahan, menawarkan kritik terhadap kecenderungan fatalistik dan materialistis. Selain itu, tawakkal memiliki implikasi psikologis yang signifikan, termasuk mengurangi kecemasan, memperkuat ketahanan emosional, dan menumbuhkan kedamaian batin di tengah ketidakpastian. Kesimpulannya, tawakkal dalam Al-Hikam mewakili konsep spiritual-etika holistik yang didasarkan secara teologis dan relevan sebagai mekanisme koping psiko-spiritual dalam kehidupan modern.